The Development of Practical Work Instruction on Material of Regeneration and Pigmentation - Dwi Candra Setiawan; As’ad Syamsul Arifin (BIOEDUKASI, 2017)
Practical work instruction is one of important teaching materials in the learning process, especially in the course that requires laboratory work. The existence of practical work instruction will really assist the students in carrying the lab work activity out. In addition, practical work instruction can also help lecturers in giving guidance during the practical activities so that the process of carrying the practical work out runs well. Based on the results of observation and personal experience of teaching teaching, some courses which include practical work do not have appropriate practical work instruction. This is why we need to develop practical work instruction on the observation process of regeneration and pigmentation of caudal fin of Zebrafish or Zebra Danio. The purpose of this research is to produce a goodpractical work instruction that is appropriate to be used by students especially in the course of animal development structure. The development of this practical work instruction used the development method of Thiagarajan which consists of define, design, develop and disseminate. However, in this research, we only proceeded until the develop stage. The object of this research was the students of IKIP Budi Utomo Malang, Biology Education Department who took the course of animal development structure. Based on the results of data analysis, we obtained that the practice manual was valid and appropriate to be used in practical work activities based on the evaluation criteria from the expert validation. Keywords: Practical Work Instruction, Thiagarajan